Stability-Indicating Assay UHPLC Method for Simultaneous Analysis of Cilnidipine and Chlorthalidone in Bulk and Pharmaceutical Matrices (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
A simple, rapid, precise and accurate stability-indicating ultra-high performance liquid chromatography (UHPLC) method was developed for the simultaneous estimation of Cilnidipine and Chlorthalidone in bulk material and pharmaceutical matrix. Accordingly, the scientific novelty of designed work was to develop a specific and precise stability-indicating UHPLC assay method for the simultaneous quantification of cited drugs in an extended-release fixed dose combinations (FDC). The reversed-phase UHPLC resolution was analyzed with the assistance of UPLC BEH C18 (150 mm 2.1 mm) with 1.7 µm particle size column at ambient temperature using a solvent system in a proportion of (70:30 % v/v) acetonitrile and water with a flow rate of 0.4 mL/min of a solvent system. The analytes were supervised at 275 nm by employing photodiode array recognition. The retention times were 1.731 ± 0.02 min and 1.061 ± 0.022 min for Cilnidipine and Chlorthalidone respectively. The Cilnidipine and Chlorthalidone have confirmed the linearity ranges of 2.0 – 12 μg/mL and 2.5 – 15 μg/mL, with 0.9998 and 0.9994 determination coefficients. The UHPLC method was effectually validated for accuracy, precision, sensitivity, robustness, ruggedness, and selectivity, and specificity. Moreover, the anticipated UHPLC method's capability to analyze the Cilnidipine and Chlorthalidone with no obstruction from degradation products.